Movement disorders in autoimmune encephalitis: Clinical spectrum, prognosis, and outcomes from an Indian cohort - Shreyashi Jha; Netravathi M; Vikram Venkappayya Holla; Nitish Kamble; Anita Mahadevan; Pramod Kumar Pal (Annals of Movement Disorders)
BACKGROUND: Antibody-mediated autoimmune encephalitis (AE) encompasses inflammatory central nervous system disorders linked etiologically with neuronal autoantibodies. Movement disorders (MDs) are common and diverse in AE, and their early identification can expedite effective management. Current literature on MDs in AE is limited to a few case reports and series, synthesized into multiple systematic reviews. Furthermore, there is a lack of literature on MDs in seronegative AE and their prognostic factors. We aimed to characterize the age-specific phenomenology, therapeutic responses, outcomes, and prognostic factors of MDs in a large cohort of patients with seropositive and seronegative AE. METHODS: This was a chart review of all patients with AE over three years (January 2018 to January 2021) at a tertiary center in Southern India. RESULTS: MDs were found to be prevalent among 47 (72.3% females) of 74 patients (63.5%) with AE. Dystonia was the most common (31.9%). Oro-facial-lingual-dyskinesias (OFLD), opsoclonus-myoclonus syndrome (OMS), and tics were prevalent in patients aged below 18 years. The most common MDs among patients with NMDAR antibody encephalitis were OFLD (60%), facio-brachial-dystonic seizures (FBDS) among all four patients with LGI-1 antibody encephalitis, myoclonus (50.0%) in the CASPR2 antibody encephalitis cohort and dystonia (80%) among patients with seronegative AE. Parkinsonism and FBDS were commonly observed in patients above 45 years of age (P < 0.001). Good response to immunotherapy was observed in 91.4%. Multivariate regression analysis demonstrated that preceding Japanese encephalitis infection, ICU stay, and delay in immunotherapy were poor prognostic factors. CONCLUSIONS: Patients above 45 years of age presented with hypokinetic MD while hyperkinetic MD were frequent in patients below 18 years of age. Hypokinetic MD had a worse prognosis.